Descriptions of four new species of Pararrhynchium de Saussure (Hymenoptera: Vespidae: Eumeninae) from China, with one newly recorded species and a key to Chinese species. (3rd April 2018) - Li, Ting-Jing; Chen, Bin
Abstract: Four new species of the genus Pararrhynchium are described and illustrated, namely P. foveolatum sp. nov. from Sichuan, China, P. impunctatum sp. nov. from Anhui, China, P. obsoletum sp. nov. from Yunnan, China, and P. parallelum sp. nov. from Guangxi, China. P. striatum Nguyen is newly recorded from China. In addition, a key to the Chinese species of the genus Pararrhynchium is updated. Type specimens of the new species are deposited in Institute of Entomology and Molecular Biology, Chongqing Normal University. http://www.zoobank.org/urn:lsid:zoobank.org:pub:74FFB035-B37E-4B99-B0F1-4DBFB3489C98